Inverse optically-induced ring currents in ring-shaped molecules - Nandipati, Krishna Reddy; Sasmal, Sudip; Vendrell, Oriol (The journal of physical chemistry letters, 2024)
Permanent electronic ring currents are supported within manifolds of ΓE degenerate excited electronic states as E± = Ex ± iEy excitations. In [ Phys. Rev. Res. 2021, 3, L042003] we showed the existence of inverse-current manifolds, where the direction of the electronic ring current in each degenerate state E± is opposite to the circular polarization of the generating light fields. This vibronic effect is caused by the exchange of orbital angular momentum between the electrons and the vibrational modes with the required symmetry. Here we consider the case of fixed nuclei and find that ring-shaped molecular systems possess inverse-current manifolds on a purely electronic-structure basis, i.e., without intervention of vibronic coupling. The effect is explained first on a tight-binding model with cyclic symmetry and then considering the ab initio electronic structure of benzene and sym-triazine. A framework for discriminating regular- and inverse-current ΓE manifolds in molecules using quantum chemistry calculations is provided.
Gesehen am 16.12.2024